PENGARUH GROUP INVESTIGATION TERHADAP MINAT BACA MAHASISWA: PERHATIAN, PERSEPSI POSITIF, PERASAAN SENANG - Eva Amalia; Ali Mustadi (ELEMENTARY SCHOOL JOURNAL PGSD FIP UNIMED, 2019)
ABSTRACTThis study aims to determine the effect of the group investigation model on students' interest in reading (attention, positive perception, and feeling happy). Research subjects 78 semester 4 students of PGSD UST. This study uses quasi-experimental methods (quasi experiment) with the design of two groups, namely the experimental class and the control class. The results showed the average reading interest of the experimental class on the pre-test 23,084 and on the post-test 26,205 so that there was influence. In the average control class the results of the 23,025 pre-test and post-test were still assumed to be 23,538, there was no increase as much as the experimental class. Based on the data it can be concluded that the group investigation model influences students' reading interest, especially positive perceptions and feelings of pleasure. Keywords: Cooperative Learning, Group Investigation  ABSTRAKPenelitian ini bertujuan mengetahui pengaruh model group investigation terhadap minat baca (perhatian, persepsi positif, dan perasaan senang) mahasiswa. Subjek penelitian 78 mahasiswa semester 4 PGSD UST. Penelitian ini menggunakan metode eksperimen semu (quasi experiment) dengan desain dua kelompok, yaitu kelas eksperimen dan kelas kontrol. Hasil penelitian menunjukkan perolehan rata-rata minat baca kelas eksperimen pada pre-test 23.084 dan pada post-test 26.205 sehingga terdapat pengaruh. Pada kelas kontrol rata-rata hasil pre-test 23.025 dan post-test tetap diangka 23.538, tidak terdapat kenaikan sebanyak kelas eksperimen. Berdasarkan data dapat disimpulkan bahwa model group investigation berpengaruh terhadap minat baca mahasiswa terutama persepsi positif dan perasaan senang.      Kata Kunci: Cooperative Learning, Group Investigation